Reviewing the practice of coming into the world with an eye to the ecology of birth - Falcicchio, Gabriella (Rivista Italiana di Educazione Familiare, 2011)
In recent decades a new perspective relevant to the processes gestation, birth and first years of life, which Michel Odent defines as “primal period”. A world renowned obstetrician, Odent resumes the tradition of non-violent delivery of F. Leboyer to enrich and renew it considering the extended ethologic, physiologic and neuro-scientific research. The vision that emerges shows that the birth is today, in the western world, an event not only medicalized and technologized, but also disturbed by routines harming the mother, the child and above all their relationship, solicits the aggressiveness potential of mankind. To ask ourselves if it is still sustainable to give birth and raise aggressive individuals goes together with the need to revise critically the practises of being born.